Soetsu Yanagi selected essays on Japanese folk crafts - Yanagi, Muneyoshi 1889-1961 (Japan library (Shuppan Bunka Sangyo Shinko Zaidan))
"The common utilitarian objects depicted in this book were considered aesthetically insignificant until the appearance of Soetsu Yanagi. It was Yanagi who discovered the beauty that could only be produced by simple, humble craftsmen repeatedly and unselfconsciously working on the same objects day after day. From this quotidian world emerged a distinctive beauty - wholesome, free, and devoid of self-awareness. To bring these crafts to the notice of the world, Yanagi established the Japan Folk Crafts Museum in 1936, from whose collection the objects illustrated herein have been chosen for inclusion by the publisher. In the essays, Yanagi expounds his philosophy of folk crafts and highlights particular pieces. Altogether, the book constitutes a penetrating insight into the world of Japanese handicrafts"--Publisher's website.